Types of Angina, Modern Methods of Diagnosis, Origin and Prevention - Boymurodova Sevara Amirulla qizi; Abduraimova Chinora Mirzakul qizi; Abdullayeva Diyora Baxtiyorovna (Journal of Science in Medicine and Life, 2025)
Angina is a clinical syndrome characterized by discomfort or tightness in the precordial region, which is caused by transient myocardial ischemia without the development of infarction. In most cases, angina attacks develop against the background of physical or emotional stress and disappear after rest or sublingual administration of nitroglycerin. The diagnosis of the disease is established on the basis of clinical manifestations, ECG changes, and various imaging methods of myocardial ischemia. Treatment may include antiplatelet drugs, nitrates, beta-blockers, calcium channel blockers, angiotensin-converting enzyme inhibitors, statins, coronary angioplasty, or coronary artery bypass grafting.